RESIKO KECELAKAAN KERJA PADA TENAGA KESEHATAN DAN PENCEGAHANNYA: SEBUAH TINJAUAN LITERATUR - Naisya Midary Mutia Pratiwi; Winda Trijayanthi Utama (Medula, 2026)
Healthcare workers represent an occupational group with a high risk of work related accidents, including biological exposure, injuries caused by sharp objects, exposure to hazardous chemical substances, and musculoskeletal disorders associated with ergonomic hazards. These risks are influenced by high workload, suboptimal use of personal protective equipment, and the incomplete implementation of safety procedures in healthcare settings. This study aims to identify the main types of hazards commonly experienced by healthcare workers and to analyze prevention strategies recommended in previous studies. The method used was a literature review by selecting relevant national and international scientific articles related to occupational accidents, needle stick injuries, chemical hazards, and ergonomic risks among healthcare workers. Selected articles were analyzed using a systematic literature review approach, focusing on key findings, contributing factors, and prevention recommendations reported in each study. The results indicate that needle stick exposure is the most frequently reported occupational accident among healthcare workers. In addition, chemical exposure from substances such as cytotoxic drugs and disinfectants, as well as musculoskeletal complaints caused by non ergonomic working techniques, are also commonly identified. Dominant contributing factors include inadequate occupational safety and health training, inconsistent use of personal protective equipment, weaknesses in healthcare facility risk management, and high workload. In conclusion, occupational accidents among healthcare workers are multifactorial and require comprehensive preventive measures through improved training, provision of safe working facilities, compliance with standard operating procedures, and strengthening of a safety culture in healthcare services.